Optimalisasi Kesehatan Ibu Muslimat melalui Senam Terstruktur di Desa Tanjung Qencono - Nanda Dwicahya; Rahmat Syaifudin (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2026)
Maternal health is an important factor in improving the quality of life of families and communities. In Tanjung Qencono Village, the low level of physical activity among Muslimat mothers affects their fitness and overall health. This community service activity aims to optimize the health of Muslimat mothers through the implementation of structured exercise carried out regularly and systematically. The methods used include socialization, training, and assistance in structured exercise for four weeks with a frequency of once a week. The participants are Muslimat mothers who actively take part in the program. Evaluation is conducted through observation, questionnaires, and measurements of fitness levels before and after the activity. The results show an increase in participant active involvement by 82%, an improvement in physical fitness by 75%, and an increase in understanding of the importance of physical activity by 88%. In addition, the participant satisfaction level reaches 87%. This activity indicates that structured exercise is able to improve health and awareness of a healthy lifestyle among Muslimat mothers despite the lower frequency. The conclusion of this activity is that structured exercise effectively optimizes the health of Muslimat mothers and has the potential to be implemented sustainably as a community empowerment program in rural areas.